FACTORS OF ECONOMIC GROWTH AND DEVELOPMENT AND THEIR APPLICATION OVERSEAS EXPERIENCE OF MATURATION (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article contains the author’s analytical opinion on factors of economic growth and development and their application overseas experience of maturation